Perancangan dan Implementasi Framework Codeigniter Manajemen POS (Point of Sale) Pada Pharmacy Legian Farma - I Nyoman Bernadus; Prastyadi Wibawa Rahayu; GN Joko Adinegara (LPPM Universitas Bina Sarana Informatika, 2025)
Research on the design and implementation of a POS (Point of Sale) management system designed to include centralized management of transaction data, inventory and financial reports. The implementation of this system is expected to minimize the risk of manual errors, increase transaction speed, and provide accurate and timely reports using the CodeIgniter Framework at Legian Farma Pharmacy. The aim of this research is to increase the operational efficiency of pharmacies by utilizing reliable and structured technology. Codeigniter was chosen as an application development framework because of its advantages in terms of simplicity, ease of use, and built-in features that support efficient system development. The research results show that the use of CodeIgniter in developing the POS (Point of Sale) system at the Legian Farma Pharmacy provides a number of benefits, including increased operational efficiency, ease of data management, as well as better scalability and security. Therefore, this framework can be considered an effective and efficient solution for POS management in the pharmaceutical sector, especially pharmacy Keywords : Codeigniter, Framework, Pharmacy, POS (Point of Sale)